Pengaruh Implementasi Prinsip Good Corporate Governance dalam Perspektif Nilai-Nilai Islam terhadap Kinerja Perusahaan - Adzra Stri Vidya Utami; Rini Lestari (UNISBA Press, 2022)
Abstract. This study aims to examine the influence of the Implementation of the Principles of Good Corporate Governance in the perspective of Islamic values affecting company performance in Sharia Banks shows that the weak application of the principles of good corporate governance so as to affect the quality of company performance in order to compete. This study aims to find out whether the implementation of the principles of good corporate governance in the perspective of Islamic values affects company performance, how the implementation of the principles of good corporate governance (GCG) in the perspective of Islamic values affects company performance, how the achievement of the successful implementation of the principles of good corporate governance (GCG) in Islamic values affects the performance of companies in the city of Bandung. This research method uses a verifiable survey with a quantitative approach. This study used primary data sources obtained through questionnaires filled out by respondents who had positions as managers from the top manager level to middle managers at Islamic banks in the city of Bandung. The sampling technique used in this study is non probability sampling, which is a purposive sampling technique. Data collection was carried out by distributing physical questionnaires and online questionnaire links (google forms) to respondents. The sample from this study was 9 Islamic banks in Bandung City and respondents in this study were 114 managers at Sharia Banks in Bandung City. Hypothesis testing was carried out using a simple regression analysis method using SPSS software version 23. The results showed that Islamic banks in the city of Bandung have the implementation of the principles of good corporate governance in the perspective of Islamic values with